Influence of Sustainable Construction Practices Awareness Level on Extent of Usage in Abuja-Nigeria - Richard Jimoh; Luqman Oyewobi; Ezekiel Ogunbode; Rasheed Isa; Abdulquadir Bilau; Aisha Yusuf (Journal of Infrastructure & Facility Asset Management, 2021)
The construction industry has been under severe pressure in recent times to adopt environmentally friendly approaches to gain a competitive advantage. This is a result of failure to select durable and sustainable materials that comply with the acceptable requirement for standards, appropriate site selection, adoption of flexible and durable designs, proper planning and management of construction activities, and proper commissioning of building systems and equipment before occupation. This study, therefore, is on the influence of sustainable construction practices awareness level on the extent of usage in Abuja – Nigeria. The study elicited data from construction professionals in Abuja-Nigeria using structured questionnaires. Based on the awareness level, managing the site for an improved environment and smart homes had mean score values of 2.23 and 2.45 respectively. In a related development, the results of the extent of usage indicated that cost efficiency and smart homes had mean score values of 2.17 and 2.97 respectively. The paired t-test showed that there was no statistically significant difference in the level of awareness and the extent of usage of sustainable construction practices in the study area. Therefore, it was concluded that the use of the sustainable practice is influenced by prior knowledge and education in terms of awareness of the existence of such practices. Hence, there is a need for proper sensitization of sustainable construction practices on their importance and necessity to humans and the environment.